Demographic and social degradation in the Lubelskie Voivodeship as a peripheral area of East Poland - Flaga, Małgorzata; Wesołowska, Monika (Bulletin of Geography. Socio-economic Series, 2018)
Eastern regions of Poland are regarded as areas where numerous unfavourable socio-economic phenomena appear and accumulate. These are the results of historical conditions as well as post-war border localization and various processes, primarily in terms of economy. The consequences of the political transformation of the state in the 1990s and profound social and economic changes in recent decades are also crucial drivers of many disadvantageous changes in the region.The article shows population processes which can be recognized nowadays in Eastern Poland, and the attention of the authors is focused on the peripheral rural areas of the region. General tendencies reported in the text are based on the cases from the Lubelskie Voivodeship where concentration of the demographic and social problems is particularly noticeable. The analyses comprise changes of population growth and its components (natural movement and migration), population structures as well as some characteristics concerning the quality and conditions of inhabitants’ lives. The main causes of negative processes shaping the population, including domestic, regional and micro-regional factors, are also presented. The final part of the article deals with the most important outcomes of population changes which are reflected in the progressing ageing of society, the decline of villages and social infrastructure, among other facts. These unfavourable phenomena are shown in the context of the future development of the region.